Implications of Feminization of Agriculture on women farmers in Anambra State, Nigeria - E N Ajani; E. M Igbokwe (Journal of Agricultural Extension, 2011)
The study surveyed 120 rural women in Anambra State, Nigeria. Majority of women farmers had taken up new roles in agriculture which were in the past regarded as male roles and included clearing of farmlands (93.3%), making of mounds and ridges (77.3%), planting of white yams (73.1%), harvesting of tree crops such as mango, oranges, cashew nut, etc (75.6%), among others. Some of the reasons indicated for taking up new roles in agriculture included increase in family responsibilities, increase in prices of food items and other household basic needs, rural-urban migration of men for white collar jobs, shortage of farm labour and education of children. The study recommends the need to formulate appropriate agricultural policies and programmes that will help to boost their productivity.